GROUNDWATER RESOURCES ASSESSMENT OF GRANULAR AQUIFERS IN GREECE - Kallioras, A.; Pliakas, F.; Marinos, P. (Bulletin of the Geological Society of Greece, 2016)
Sound groundwater resources management is a matter of paramount importance in Circum-Mediterranean, for the ecologic status of the underlying aquifer systems. Freshwater resources in Greece are identified within all types of aquifer formations, however two distinct types are the ones that draw the attention of the scientific and the engineering community; the granular as well as the karst aquifers. This paper describes the groundwater resources potential that are found within granular aquifer formations, in combination with the major environmental threats associated with their exploitation and management.